Composite particle for non-aqueous electrolyte rechargeable battery, method for preparing same, positive electrode, and non-aqueous electrolyte rechargeable battery
By using composite particles of metal hydroxide and flame retardant in rechargeable lithium-ion batteries, the problem of rising internal temperature of the battery is solved, and the cycling characteristics of the battery is maintained, achieving a dual improvement in safety and performance.
Patent Information
- Application Number
- CN202411115799.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-25
- Filing Date
- 2024-08-14
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art has shortcomings in reducing the internal temperature increase of rechargeable lithium-ion batteries, and there are problems with deterioration in cycling characteristics.
By using composite particles containing metal hydroxide and flame retardant in a nonaqueous electrolyte rechargeable battery, the specific amount of elements of the flame retardant component is adjusted to reduce or inhibit the rise in the internal temperature and to maintain the circulation of the battery characteristic.
It realizes the reduction of the internal temperature of the battery under a high temperature environment, avoids the risk of short circuit caused by the increase in temperature, and maintains the cycle characteristics and performance of the battery.
Smart Images

Figure CN119495807A_ABST
Abstract
Description
[0001] This application claims the benefit of priority from Japanese Patent Application No. 2023-131857 filed in the Japan Patent Office on August 14, 2023, and Korean Patent Application No. 10-2024-0055545 filed in the Korean Intellectual Property Office on April 25, 2024, the entire contents of which are incorporated herein by reference. Technical Field
[0002] Examples of the present disclosure relate to composite particles for a nonaqueous electrolyte rechargeable battery and a nonaqueous electrolyte rechargeable battery including the composite particles. Background Art
[0003] Nonaqueous electrolyte rechargeable batteries (including, for example, rechargeable lithium ion batteries) are widely used as power sources for smartphones, notebook computers, and the like, and for large batteries such as vehicles, for example.
[0004] On the other hand, rechargeable lithium ion batteries have the advantage of high energy density, but since rechargeable lithium ion batteries use non-aqueous electrolytes, sufficient safety measures are required. In addition, with the recent increase in battery size, ensuring safety is a noteworthy aspect.
[0005] For example, when a rechargeable lithium ion battery is placed in a high temperature environment, there is a possibility that the positive electrode of the rechargeable lithium ion battery generates heat, or the electrolyte generates heat due to an oxidative decomposition reaction caused by oxygen free radicals generated from the positive electrode, causing the internal temperature of the battery to rise.
[0006] If the internal temperature of the battery becomes substantially high due to such reasons, a short circuit due to shrinkage of a separator provided in the rechargeable lithium ion battery may occur, and there is a risk that the internal temperature of the battery may gradually increase.
[0007] Therefore, as a method of ensuring safety by reducing or suppressing the increase in the internal temperature of a rechargeable lithium ion battery, it has been proposed to incorporate a binder including a radical scavenger having a radical scavenging ability (such as a phosphate ester) (Patent Document 1, Japanese Patent Publication No. 2011-159484) or metal hydroxide particles having an endothermic property (Patent Document 2, Japanese Patent Publication No. 2016-162528; and Patent Document 3, Japanese Patent Publication No. 2011-258481). Summary of the invention
[0008] However, the internal temperature increase of the battery cannot be sufficiently reduced or suppressed simply by incorporating the radical scavenger described in Patent Document 1 and the metal hydroxide particles described in Patent Document 2 and Patent Document 3 into a non-aqueous electrolyte rechargeable battery such as a rechargeable lithium ion battery. In addition, by including the metal hydroxide particles or the radical scavenger, there are challenges such as deterioration of the cycle characteristics (discharge capacity retention rate) when the charge and discharge cycles are repeated.
[0009] As a result, the exemplary embodiments of the present disclosure solve the above challenges and achieve a further effect of reducing or suppressing an internal temperature increase by including a metal hydroxide and a flame retardant component and adjusting the amount of specific elements constituting the flame retardant component within a predetermined range.
[0010] That is, the exemplary embodiment includes the following configurations.
[0011] Composite particles for non-aqueous electrolyte rechargeable batteries according to some example embodiments include a metal hydroxide and a flame retardant component, wherein the flame retardant component contains phosphorus element, phosphorus element and boron element, or phosphorus element and bromine element, and a content of the phosphorus element, a sum of the contents of the phosphorus element and the boron element, or a sum of the contents of the phosphorus element and the bromine element is greater than or equal to about 18 wt % and less than or equal to about 30 wt % based on 100 wt % of the composite particles for non-aqueous electrolyte rechargeable batteries.
[0012] The amount of P2 (MS1) desorbed from the composite particles from about 80°C to about 1400°C as determined by thermal desorption gas mass spectrometry (TDS-MS) may be greater than or equal to about 600×10 -6 mol / g and less than or equal to about 2000×10 -6 mol / g, and the amount of H2O desorbed from the composite particles from about 80°C to about 200°C as determined by TDS-MS (MS2) may be greater than or equal to about 50×10 -6 mol / g and less than or equal to about 1000×10 -6 mol / g.
[0013] The amount of CH4 desorbed from the composite particles from about 80°C to about 1400°C as determined by TDS-MS (MS3) may be greater than or equal to about 30×10 -6 mol / g and less than or equal to about 400×10 -6 mol / g, the amount of CH3OH desorbed from the composite particles from about 80°C to about 1400°C as determined by TDS-MS (MS4) may be greater than or equal to about 500×10 -6 mol / g and less than or equal to about 2500×10 -6mol / g, and the amount of C6H6(MS5) desorbed from the composite particles from about 80°C to about 1400°C as determined by TDS-MS may be greater than or equal to about 100×10 -6 mol / g and less than or equal to about 2500×10 -6 mol / g.
[0014] The ratio of the amount of desorbed gas can satisfy the formula (1):
[0015] 0.6≤(MS1 / MS2)≤10.0…(1).
[0016] The Brunauer Emmett Teller (BET) specific surface area calculated by an adsorption isotherm measured via adsorption of nitrogen may be greater than or equal to about 8 m 2 / g and less than or equal to about 80m 2 / g.
[0017] The 50% integral value of the volume-based particle size distribution of the composite particles (D 50 ) may be greater than or equal to about 0.05 μm and less than or equal to about 10 μm.
[0018] The metal hydroxide may include at least one of aluminum hydroxide, pseudoboehmite, boehmite, activated alumina, and kaolinite.
[0019] The aluminum element content as determined by inductively coupled plasma optical emission spectroscopy (ICP-AES) may be greater than or equal to about 5 wt % and less than or equal to about 30 wt %.
[0020] A positive electrode for a nonaqueous electrolyte rechargeable battery according to example embodiments includes a positive electrode collector and a positive electrode mixture layer on the positive electrode collector, wherein the positive electrode mixture layer includes a positive electrode active material and the aforementioned composite particles.
[0021] A nonaqueous electrolyte rechargeable battery according to example embodiments includes a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte, wherein the positive electrode is the aforementioned positive electrode.
[0022] The method of preparing composite particles for non-aqueous electrolyte rechargeable batteries includes mixing metal hydroxide particles and a flame retardant and heating the metal hydroxide particles and the flame retardant to prepare the aforementioned composite particles.
[0023] According to the composite particles for non-aqueous electrolyte rechargeable batteries constructed according to example embodiments, by including a sufficient amount of a flame retardant component and a metal hydroxide, an increase in the internal temperature of the battery can be reduced or suppressed, and deterioration in the cycle characteristics of the battery due to the inclusion of these substances can be reduced or suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a graph showing cycle characteristics in Examples and Comparative Examples.
[0025] Figure 2 is a graph showing the effect of reducing or suppressing heat in Examples and Comparative Examples. DETAILED DESCRIPTION
[0026] Hereinafter, example embodiments will be described in detail so that those skilled in the art can easily implement the example embodiments. However, the present disclosure may be embodied in many different forms and is not to be construed as limited to the example embodiments set forth herein.
[0027] The terms used herein are used to describe the embodiments and are not intended to limit the present invention. Unless the context clearly indicates otherwise, a singular expression includes a plural expression.
[0028] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like, of the components.
[0029] Here, it should be understood that terms such as "includes," "comprising," or "having" are intended to indicate the presence of embodied features, quantities, steps, elements, or a combination thereof, but it does not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or a combination thereof.
[0030] In the drawings, the thickness of layers, films, panels, regions, etc., are exaggerated for clarity, and like reference numerals denote like elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or there can be intervening elements. Conversely, when an element is referred to as being "directly on" another element, there are no intervening elements.
[0031] In addition, the "layer" here includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a part of the surface.
[0032] In addition, the particle size can be an average particle size and the average particle size can be measured by methods well known to those skilled in the art, for example, it can be measured by a particle size analyzer, or it can be measured by a transmission electron microscope image or a scanning electron microscope image. Alternatively, it is possible to measure by using a dynamic light scattering method, perform data analysis, count the number of particles in each particle size range, and calculate the average particle size value. Unless otherwise defined, the average particle size can refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution (D 50As used herein, when no definition is otherwise provided, the average particle size refers to the diameter (D) of particles having a cumulative volume of 50% by volume in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of about 20 particles in a scanning electron microscope image. 50 ).
[0033] Here, “or” is not interpreted as an exclusive meaning, for example, “A or B” is interpreted as including A, B, A+B, etc.
[0034] The term "metal" is interpreted as a concept including common metals, transition metals, and metalloids (semimetals).
[0035] When the term "about" or "substantially" is used in conjunction with a numerical value in this specification, it is intended that the relevant numerical value includes a tolerance of ±10% around the stated numerical value. When a range is specified, the range includes all values therebetween (such as in increments of 0.1%).
[0036] Hereinafter, a configuration of a nonaqueous electrolyte rechargeable battery according to example embodiments will be described.
[0037] 1. Basic structure of non-aqueous electrolyte rechargeable battery
[0038] The nonaqueous electrolyte rechargeable battery according to this example embodiment is a rechargeable lithium ion battery including a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte.
[0039] The shape of the rechargeable lithium ion battery is not particularly limited, and may be, for example, cylindrical, square, laminated, or button-shaped.
[0040] 1-1. Positive electrode
[0041] The positive electrode includes a positive electrode current collector and a positive electrode mixture layer on the positive electrode current collector.
[0042] The positive electrode current collector may be or include any material as long as the material is a conductor, and is, for example, plate-shaped or thin, and may be made of aluminum, stainless steel, nickel-plated steel, or the like.
[0043] The positive electrode mixture layer may include at least a positive electrode active material, and may further include a conductive agent and a positive electrode binder.
[0044] The positive electrode active material may be or include, for example, a transition metal oxide or a solid solution oxide including lithium, and is not particularly limited as long as the material can electrochemically intercalate and deintercalate lithium ions. Examples of transition metal oxides including lithium may include Li 1.0 Ni 0.88 Co 0.1 Al 0.01 Mg0.01 O2, etc. In addition, examples of transition metal oxides containing lithium may include LiCo-based composite oxides such as LiCoO2, LiNi x Co y Mn z O2, a LiNi based composite oxide such as LiNiO2, or a LiMn based composite oxide such as LiMn2O4. Examples of solid solution oxides may include Li a Mn x Co y Ni z O2 (1.150≤a≤1.430, 0.45≤x≤0.6, 0.10≤y≤0.15, 0.20≤z≤0.28), or LiMn 1.5 Ni 0.5 On the other hand, the content (content ratio) of the positive electrode active material is not particularly limited as long as it is suitable for the positive electrode mixture layer of the nonaqueous electrolyte rechargeable battery. In addition, these compounds may be used alone or in mixture of plural types.
[0045] The conductive agent is not particularly limited as long as the conductive agent improves the conductivity of the positive electrode. Examples of the conductive agent may include a conductive agent containing at least one of carbon black, natural graphite, artificial graphite, fiber carbon, and flaky carbon. Examples of carbon black may include furnace black, channel black, thermal black, Ketjen black, and acetylene black.
[0046] Examples of the fibrous carbon may include carbon nanotubes and carbon nanofibers, and examples of the flaky carbon include graphene and the like.
[0047] The content of the conductive agent in the positive electrode mixture layer is not particularly limited, but can be greater than or equal to about 0.1wt% and less than or equal to about 5wt% (greater than or equal to about 0.5wt% and less than or equal to about 3wt%) based on the total amount of the positive electrode mixture layer, and both conductivity and battery capacity are achieved when within any of the above ranges.
[0048] The positive electrode binder may include, for example, fluorine-containing resins such as at least polyvinylidene fluoride, vinyl-containing resins such as styrene-butadiene rubber, ethylene-propylene diene terpolymers, acrylonitrile-butadiene rubber, fluororubber, polyvinyl acetate, polymethyl methacrylate, polyethylene, polyvinyl alcohol, carboxymethyl cellulose, carboxymethyl cellulose derivatives (salts of carboxymethyl cellulose, etc.), nitrocellulose, etc. The positive electrode binder may be or include any material capable of binding the positive electrode active material and the conductive agent to the positive electrode current collector, and is not particularly limited.
[0049] 1-2. Negative electrode
[0050] The negative electrode includes a negative electrode current collector and a negative electrode mixture layer on the negative electrode current collector.
[0051] The negative electrode current collector may be or include any material as long as the material is a conductor, and may be plate-shaped or thin and made of copper, stainless steel, nickel-plated steel, or the like.
[0052] The negative electrode mixture layer may include a negative electrode active material, and may further include a conductive agent and a negative electrode binder.
[0053] The negative electrode active material is not particularly limited as long as the material can electrochemically intercalate and deintercalate lithium ions, but may be or include, for example, a graphite active material (artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite), a Si-based active material or a Sn-based active material (for example, a mixture of fine particles of silicon (Si) or fine particles of tin (Sn) or fine particles of their oxides and a graphite active material, microparticles of silicon or tin, an alloy including silicon or tin as a matrix material), such as Li4Ti5O 12 As the negative electrode active material, one of the above examples can be used, or two or more types can be used in combination. On the other hand, silicon oxide can be made of SiO x (0<x≤2) indicates.
[0054] The conductive agent is not particularly limited as long as the conductive agent increases the conductivity of the negative electrode, and for example, the same conductive agent as described in the section of the positive electrode can be used.
[0055] The content of the conductive agent in the negative electrode mixture layer is not particularly limited, but can be greater than or equal to about 0.1wt% and less than or equal to about 5wt% (or greater than or equal to about 0.5wt% and less than or equal to about 3wt%) based on the total weight of the negative electrode mixture layer, and both conductivity and battery capacity are achieved when within any of the above ranges.
[0056] The negative electrode binder may be capable of binding the negative electrode active material and the conductive agent to the negative electrode current collector without particular limitation. The negative electrode binder may be or include, for example, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), styrene-butadiene copolymer (SBR), metal salt of carboxymethyl cellulose (CMC), etc. The binder may be used alone or in a mixture of two or more types.
[0057] 1-3. Diaphragm
[0058] The separator is not particularly limited, and any separator can be used as long as it is a separator for a rechargeable lithium ion battery. The separator may be or include at least one of a porous film, a nonwoven fabric, etc. that exhibits improved, desired, or favorable high-rate discharge performance. The resin constituting the separator may be or include, for example: a polyolefin resin, such as at least one of polyethylene, polypropylene, etc.; a polyester resin, such as at least one of polyethylene terephthalate and polybutylene terephthalate; polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-perfluorovinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-trifluoroethylene copolymer, vinylidene fluoride-hexafluoroacetone copolymer, vinylidene fluoride-ethylene copolymer, vinylidene fluoride-propylene copolymer, vinylidene fluoride-trifluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-ethylene-tetrafluoroethylene copolymer, etc. On the other hand, the porosity of the separator is not particularly limited, and the porosity of a separator of a conventional rechargeable lithium ion battery can be arbitrarily applied.
[0059] The separator may also include a surface layer covering the surface of the porous film or nonwoven fabric. The surface layer may include a binder for fixing the battery element by adhering to the electrode. Examples of the binder may include at least one of a vinylidene fluoride-hexafluoropropylene copolymer, an acid-modified product of a vinylidene fluoride polymer, and a styrene-(meth)acrylate copolymer.
[0060] 1-4. Non-aqueous electrolyte
[0061] As the nonaqueous electrolyte, the same nonaqueous electrolyte as has been conventionally used for rechargeable lithium ion batteries can be used without particular limitation. The nonaqueous electrolyte has a composition in which an electrolyte salt is included in a nonaqueous solvent which is a solvent of the electrolyte. Examples of non-aqueous solvents may include: cyclic carbonates, such as at least one of propylene carbonate, ethylene carbonate, butylene carbonate, chloroethylene carbonate, fluoroethylene carbonate and vinylene carbonate; cyclic esters, such as γ-butyrolactone and γ-valerolactone; chain carbonates, such as dimethyl carbonate, diethyl carbonate or ethyl methyl carbonate; chain esters, such as methyl formate, methyl acetate, methyl butyrate, ethyl propionate, propyl propionate; ethers, such as tetrahydrofuran or its derivatives, 1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, 1,4-dibutoxyethane, methyl diglyme, ethylene glycol monopropyl ether or propylene glycol monopropyl ether; nitriles, such as acetonitrile and benzonitrile; dioxolane or its derivatives; ethylene sulfide; cyclopentane; sultone or its derivatives, which may be used alone or in a mixture of two or more. On the other hand, when two or more types of nonaqueous solvents are mixed and used, the mixing ratio of each nonaqueous solvent may be a mixing ratio that can be used in a conventional rechargeable lithium ion battery.
[0062] Examples of electrolyte salts may include: inorganic ionic salts containing at least one of lithium (Li), sodium (Na), and potassium (K), such as LiClO4, LiBF4, LiAsF6, LiPF6, LiPF 6-x (C n F2 n+1 ) x [provided that 1 < x < 6 and n = 1 or 2], LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 , NaClO4, NaI, NaSCN, NaBr, KClO4, KSCN; or organic ionic salts, such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiC(C2F5SO2)3, (CH3)4NBF4, (CH3)4NBr, (C2H5)4NClO4, (C2H5)4NI, (C3H7)4NBr, (n-C4H9)4NClO4, (n-C4H9)4NI, (C2H5)4N - maleate, (C2H5)4N - benzoate, (C2H5)4N - phthalate, lithium stearyl sulfonate, lithium octyl sulfonate, lithium dodecylbenzenesulfonate, etc., and these ionic compounds can also be used alone or as a mixture of two or more types. The concentration of the electrolyte salt can be the same as that of the non-aqueous electrolyte used in a conventional rechargeable lithium-ion battery and is not particularly limited. In an exemplary embodiment, it is desirable to use a non-aqueous electrolyte containing the aforementioned lithium compound (electrolyte salt) at a concentration greater than or equal to about 0.8 mol / L and less than or equal to about 1.5 mol / L.
[0063] In an example, various additives can be added to the non-aqueous electrolyte. Examples of such additives may include, for example, at least one of a negative electrode acting additive, a positive electrode acting additive, an ester additive, a carbonate additive, a sulfate ester additive, a phosphate ester additive, a borate ester additive, an acid anhydride additive, and an electrolyte additive. At least one of these additives can be added to the non-aqueous electrolyte, and multiple types of additives can be added.
[0064] 2. Structure of the non-aqueous electrolyte rechargeable battery according to this embodiment
[0065] Hereinafter, the characteristic structure of the non-aqueous electrolyte rechargeable battery according to the exemplary embodiment will be described.
[0066] In addition to the aforementioned components, the positive electrode mixture layer of the nonaqueous electrolyte rechargeable battery according to example embodiments includes composite particles for nonaqueous electrolyte rechargeable batteries (also simply referred to as composite particles) constituting a heat reduction or suppression additive to reduce or suppress an internal temperature increase of the battery.
[0067] These composite particles are manufactured by heating at least a metal hydroxide capable of absorbing heat by an endothermic reaction and a flame retardant having a free radical capture ability so that they are combined. These composite particles are combined in a state where the metal hydroxide and the flame retardant are mixed as evenly as possible. For example, composite particles are prepared by collecting a plurality of metal hydroxide particles and a flame retardant component derived from the above-mentioned flame retardant included on the surface and inside of the plurality of metal hydroxide particles. Here, "composite" refers to, for example, that the flame retardant component is chemically bonded to each other by functional groups (for example, hydroxyl and phosphate groups, etc.) included on the surface and inside of the metal hydroxide particles, thereby forming a plurality of particles into an aggregate. The chemical bond here includes not only covalent bonds, but also various bonds, such as ionic bonds, coordination bonds and metallic bonds. The bonding state between the particles can be confirmed, for example, by X-ray photoelectron spectroscopy.
[0068] The particle size of the composite particles may be such that the 50% integral value (D 50 ) may be greater than or equal to about 0.05 μm and less than or equal to about 10 μm. The D 50 It may be greater than or equal to about 0.08 μm and less than or equal to about 9 μm (or greater than or equal to about 0.1 μm and less than or equal to about 8.5 μm).
[0069] The particle size of the composite particles can be controlled by the preparation conditions of the composite particles. For example, if the temperature used to prepare the composite particles is increased, or the stirring speed is increased, the particle size of the composite particles tends to become smaller. For example, the particle size of the composite particles can be made smaller than the particle size of the metal hydroxide used as the starting material.
[0070] In addition, the BET specific surface area of the composite particles calculated by an adsorption isotherm measured by adsorbing nitrogen to the composite particles may be greater than or equal to about 8 m 2 / g and less than or equal to about 80m 2 / g, greater than or equal to about 10m 2 / g and less than or equal to about 75m 2 / g, or greater than or equal to about 15m 2 / g and less than or equal to about 75m 2 / g.
[0071] The metal hydroxide is not particularly limited as long as the metal hydroxide is an endothermic material that can cause an endothermic reaction. Examples of metal hydroxides may include aluminum hydroxide, pseudoboehmite, boehmite, activated alumina, and kaolinite. These may be used alone, or two or more types may be used together.
[0072] The 50% integral value (D 50 ) may be greater than or equal to about 10 nm and less than or equal to about 10 μm, greater than or equal to about 0.1 μm and less than or equal to about 8 μm, or greater than or equal to about 0.5 μm and less than or equal to about 5 μm.
[0073] Based on the total amount of the composite particles (100 wt %), the content of the hydroxide particles in the composite particles may be in a range of greater than or equal to about 1 wt % and less than or equal to about 60 wt %, greater than or equal to about 5 wt % and less than or equal to about 50 wt %, or greater than or equal to about 10 wt % and less than or equal to about 40 wt %.
[0074] The flame retardant may have a free radical capture capability of capturing free radicals (such as oxygen free radicals) generated in the positive electrode mixture layer, and may include at least one of, for example, phosphoric acid, phosphate, phosphonic acid, phosphonate, phosphinic acid and phosphinic acid esters, which may be combined with metal hydroxides to form a functional group including phosphorus (P) elements. In addition, the flame retardant may further include, for example, boric acid or bromic acid. In addition, the flame retardant may further include, for example, boric acid (for example, boric acid or substituted boric acid) or bromic acid. The substituted boric acid may be a C1-C10 alkyl boronic acid or a C6-C10 aryl boronic acid.
[0075] Examples of the phosphoric acid ester may include at least one of phenyl phosphate, diphenyl phosphate, and triphenyl phosphate.
[0076] Examples of the phosphonate may include at least one of phenylphosphonic acid and methylphosphonic acid.
[0077] Examples of the phosphinate may include methylphosphinic acid.
[0078] For the composite particles, the content of the P (phosphorus) element, the sum of the contents of the P (phosphorus) element and the B (boron) element, or the sum of the contents of the P (phosphorus) element and the Br (bromine) element measured by inductively coupled plasma emission spectrometry (ICP-AES) may be greater than or equal to about 18 wt% and less than or equal to about 30 wt% based on the total amount (100 wt%) of the composite particles. The content of these elements or each sum of the contents of these elements may be greater than or equal to about 18 wt% and less than or equal to about 25 wt%.
[0079] The content of the P (phosphorus) element in the composite particles may be greater than or equal to about 5 wt % and less than or equal to about 30 wt %, or greater than or equal to about 8 wt % and less than or equal to about 30 wt %.
[0080] The content of B (boron) element in the composite particles may be 0, but may be greater than or equal to about 1 wt % and less than or equal to about 25 wt %, or greater than or equal to about 5 wt % and less than or equal to about 15 wt %.
[0081] The content of Br (bromine) element in the composite particles may be 0, but may also be greater than or equal to about 1 wt % and less than or equal to about 25 wt %, or greater than or equal to about 5 wt % and less than or equal to about 10 wt %.
[0082] The content of Al (aluminum) element in the composite particles measured by ICP-AES may be 0, but may also be greater than or equal to about 1 wt % and less than or equal to about 30 wt %, greater than or equal to about 3 wt % and less than or equal to about 20 wt %, greater than or equal to about 5 wt % and less than or equal to about 30 wt %, or greater than or equal to about 5 wt % and less than or equal to about 15 wt %.
[0083] Due to various modifying groups, the composite particles can have various desorbed gases in amounts within the following ranges.
[0084] When the composite particles are heated from about 80° C. to about 1400° C., the amount of P2 gas desorbed from the composite particles (referred to as MS1) as measured using thermal desorption gas mass spectrometry (TDS-MS) may be greater than or equal to about 600×10 -6 mol / g and less than or equal to about 2000×10 -6 mol / g, and when the composite particles are heated from about 80°C to about 200°C, the amount of H2O gas desorbed from the composite particles measured by TDS-MS (referred to as MS2) may be greater than or equal to about 50×10 -6 mol / g and less than or equal to about 1000×10 -6 mol / g.
[0085] MS1 may be greater than or equal to about 620×10 -6 mol / g and less than or equal to about 1900×10 -6 mol / g, or greater than or equal to about 630×10 -6 mol / g and less than or equal to about 1800×10 -6 mol / g.
[0086] MS2 can be greater than or equal to about 100×10 -6 mol / g and less than or equal to about 950×10 -6mol / g, or greater than or equal to about 200×10 -6 mol / g and less than or equal to about 900×10 -6 mol / g.
[0087] In addition, the ratio of the amount of desorbed gas (MS1 / MS2) may be greater than or equal to about 0.6 and less than or equal to about 10.0, greater than or equal to about 0.7 and less than or equal to about 5.0, or greater than or equal to about 0.8 and less than or equal to about 4.0. By ensuring that the ratio of the amount of desorbed gas (MS1 / MS2) satisfies the above range, both the effect of reducing or suppressing the temperature increase caused by increasing the content of the flame retardant component in the composite particles and the battery performance can achieve a better balance.
[0088] Increasing the content of elemental phosphorus in the composite particles improves the effect of reducing or suppressing the temperature rise inside the battery. On the other hand, if the amount of flame retardant (such as phosphoric acid or phosphonic acid) added is increased in order to increase the content of elemental phosphorus, the hydrophilicity of the composite particles is increased, making it challenging to uniformly mix the composite particles in the slurry used to form the positive electrode mixture layer. Example embodiments include not only the use of phosphoric acid and phosphonic acid with a large content of elemental phosphorus, but also the use of flame retardants with hydrophobic groups (such as phosphates and phosphonates), resulting in the ability to reduce or suppress excessive increases in hydrophilicity while increasing the content of elemental phosphorus. The content of hydrophobic groups in the composite particles is evaluated by the amount of various desorbed gases from each hydrophobic group in the composite particles, and thus the amount of various desorbed gases can meet the following ranges.
[0089] When the composite particles are heated from about 80° C. to about 1400° C., the amount of CH4 gas desorbed from the composite particles measured by TDS-MS (referred to as MS3) may be equal to 0, but may also be greater than or equal to about 30×10 -6 mol / g and less than or equal to about 400×10 -6 mol / g, greater than or equal to about 40×10 -6 mol / g and less than or equal to about 350×10 -6 mol / g, or greater than or equal to about 50×10 -6 mol / g and less than or equal to about 300×10 -6 mol / g.
[0090] The amount of CH3OH desorbed, measured in the same manner (referred to as MS4), can be 0 but can also be greater than or equal to about 500×10 -6 mol / g and less than or equal to about 2500×10 -6 mol / g, greater than or equal to about 600×10 -6 mol / g and less than or equal to about 2450×10-6 mol / g, or greater than or equal to about 700×10 -6 mol / g and less than or equal to about 2400×10 - 6 mol / g.
[0091] If the composite particles are modified with a functional group including a phenyl group among the hydrophobic groups, when a slurry is manufactured using a non-aqueous solvent such as N-methyl-2-pyrrolidone (NMP), the composite particles can be more dispersed in the solvent.
[0092] Thus, the amount of C6H6 desorbed from about 80°C to about 1400°C as determined by TDS-MS (referred to as MS5) of the above composite particles may be 0, but may also be greater than or equal to about 100×10 -6 mol / g and less than or equal to about 2500×10 - 6 mol / g, greater than or equal to about 300×10 -6 mol / g and less than or equal to about 2400×10 -6 mol / g, or greater than or equal to about 600×10 -6 mol / g and less than or equal to about 2300×10 -6 mol / g.
[0093] The content of the composite particles in the positive electrode mixture layer may be in a range of about 0.1 wt% or more and about 5 wt% or less, about 0.2 wt% or more and about 3 wt% or more, or about 0.5 wt% or more and about 2 wt% or less, based on 100 wt% of the total weight of the positive electrode mixture layer. Within any of the above content ranges of the composite particles, sufficient heat reduction or suppression effects and good battery performance may be achieved.
[0094] In addition, the content of the composite particles for non-aqueous electrolyte rechargeable batteries based on the total weight of the non-aqueous electrolyte rechargeable battery may vary depending on the purpose of the non-aqueous electrolyte rechargeable battery, and is not limited to the following range, but for example, when the total mass of the rechargeable battery is 100wt%, the content of the composite particles for non-aqueous electrolyte rechargeable batteries included in the non-aqueous electrolyte rechargeable battery may be greater than or equal to about 0.01wt% and less than or equal to about 5.0wt%, greater than or equal to about 0.02wt% and less than or equal to about 2.0wt%, or greater than or equal to about 0.1wt% and less than or equal to about 0.5wt%.
[0095] 3. Method for manufacturing a non-aqueous electrolyte rechargeable battery according to an example embodiment
[0096] Hereinafter, a method of manufacturing a nonaqueous electrolyte rechargeable battery according to example embodiments is described.
[0097] 3-1. Preparation method of composite particles
[0098] Composite particles for a non-aqueous electrolyte rechargeable battery according to example embodiments may be prepared by mixing metal hydroxide particles and a flame retardant, and heating the metal hydroxide particles and the flame retardant.
[0099] The mixing can be performed, for example, by the steps of dispersing the metal hydroxide particles and the flame retardant in an appropriate solvent, heating the dispersion to a temperature of about 40° C. or higher and about 100° C. or lower, reacting at the same temperature for about 1 hour or longer and about 48 hours or shorter, and filtering with filter paper to obtain composite particles.
[0100] The solvent may be water, or a mixture of water and an alcoholic organic solvent (such as at least ethanol or 2-propanol, for example).
[0101] The heating temperature may be greater than or equal to about 60° C. and less than or equal to about 80° C., and the heating time (reaction time) may be greater than or equal to about 5 hours and less than or equal to about 30 hours.
[0102] In order to prepare composite particles that are more modified by the flame retardant component derived from the flame retardant for the metal hydroxide, it may be advantageous to use a metal hydroxide having a BET specific surface area as large as possible as a starting material and mix the metal hydroxide having a relatively large BET specific surface area with the flame retardant to set the specific surface area of the composite particles within the above range. The BET specific surface area of the composite particles has a tendency to decrease when the amount of the flame retardant added to the metal hydroxide increases or when the reaction time is prolonged when the metal hydroxide and the flame retardant are combined. Accordingly, the BET specific surface area of the composite particles can be adjusted by changing these conditions, so the BET specific surface area of the metal hydroxide as the starting material is not particularly limited, but the BET specific surface area of the metal hydroxide can be, for example, greater than or equal to about 100 m 2 / g and less than or equal to about 500m 2 / g.
[0103] 3-2. Method for manufacturing positive electrode
[0104] The positive electrode can be manufactured as follows. A positive electrode slurry is formed by dispersing a mixture of a positive electrode active material, a conductive agent, a positive electrode binder and composite particles in a desired ratio in a solvent for a positive electrode slurry. The positive electrode slurry is coated on a positive electrode current collector and dried to form a positive electrode mixture layer. In various examples, the coating method is not particularly limited. The coating method may include, for example, a blade coater method, a gravure coater method, a reverse roll coater method, a slit die coater method, and the like. Each of the following coating processes is also performed by the same method. The positive electrode material mixture layer is pressed by a press to have a desired density. Thus, a positive electrode is manufactured.
[0105] 3-3. Method for manufacturing negative electrode
[0106] The negative electrode is also manufactured similarly to the positive electrode. The negative electrode slurry is prepared by dispersing a mixture of materials constituting the negative electrode mixture layer in a solvent for the negative electrode slurry. The negative electrode mixture layer is formed by coating the negative electrode slurry on the negative electrode current collector and drying the negative electrode slurry and the negative electrode current collector. The negative electrode mixture layer is pressed by a press to have a desired density. Thus, the negative electrode is manufactured.
[0107] 3-4. Method for manufacturing a non-aqueous electrolyte rechargeable battery
[0108] The electrode structure is manufactured by placing a separator between the positive electrode and the negative electrode. The electrode structure can be processed into a desired shape (e.g., a cylindrical shape, a prism shape, a laminated shape, a button shape, etc.) and inserted into a container of the above shape. A non-aqueous electrolyte is inserted into a corresponding container to impregnate the electrolyte into each hole in the separator or the gap between the positive electrode and the negative electrode. Thus, a rechargeable lithium ion battery is manufactured.
[0109] 4. Effects of the exemplary embodiments
[0110] According to the non-aqueous electrolyte rechargeable battery constructed as described above, even in an environment where the internal temperature may rise due to battery abnormalities such as internal short circuits, the increase in the internal temperature of the non-aqueous electrolyte rechargeable battery can be sufficiently reduced or suppressed, and in addition, the deterioration of the cycle characteristics of the non-aqueous electrolyte rechargeable battery can be reduced or suppressed by including a heat reducing or suppressing additive that reduces or suppresses heat generation.
[0111] In addition, by including a heat reduction or suppression additive that reduces or suppresses heat generation, degradation of the cycle characteristics of the nonaqueous electrolyte secondary battery can be reduced or suppressed.
[0112] 5. Another Example Embodiment
[0113] The present disclosure is not limited to the foregoing exemplary embodiments.
[0114] In the foregoing example embodiment, the case where the positive electrode includes the composite particles according to the example of the present disclosure has been described, but the negative electrode may also include the composite particles. In the case where the composite particles are included in the negative electrode, it is desirable to set the content equivalent to the content in the case where the composite particles are included in the positive electrode.
[0115] In addition, the composite particles may be included in the electrolyte, or may be included in a plurality of locations in the positive electrode, the negative electrode, and the electrolyte.
[0116] When the negative electrode includes the composite particles for nonaqueous electrolyte rechargeable batteries, the content of the composite particles for nonaqueous electrolyte rechargeable batteries based on the total weight of the negative electrode may be in the same or similar range as that of the composite particles for the positive electrode.
[0117] When the electrolyte includes the composite particles for a nonaqueous electrolyte rechargeable battery, the content of the composite particles for a nonaqueous electrolyte rechargeable battery may be in the range of about 0.1 wt % to about 10.0 wt % when the total mass of the electrolyte is 100 wt %.
[0118] Additionally, the present disclosure is not limited to these exemplary embodiments, but various modifications may be made without departing from the purpose.
[0119] [Example]
[0120] Hereinafter, the present disclosure will be described in more detail according to the following examples. However, the present invention is not limited to the following examples.
[0121] Manufacturing of composite particles
[0122] Example 1
[0123] As a starting material, 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of phenyl phosphate and 2.5g of phosphonic acid, and dispersed them in a mixed solution of 50cc of ethanol and pure water (mixing volume ratio 1:1). The dispersion was heated at 70°C for 24 hours, filtered with water and ethanol, washed with water and ethanol, and the solid on the filter paper was vacuum dried to obtain composite particles AA.
[0124] Example 2
[0125] Composite particles AB were obtained in the same manner as in Example 1 except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of diphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0126] Example 3
[0127] Composite particles AC were obtained in the same manner as in Example 1, except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of triphenyl phosphate and 2.5g of phosphonic acid were used as starting materials.
[0128] Example 4
[0129] Composite particles AD were obtained in the same manner as in Example 1 except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphonic acid as starting materials.
[0130] Example 5
[0131] Composite particles AE were obtained in the same manner as in Example 1, except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphoric acid as starting materials.
[0132] Example 6
[0133] Composite particles AF were obtained in the same manner as in Example 1, except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphinic acid as starting materials.
[0134] Example 7
[0135] Composite particles AG were obtained in the same manner as in Example 1 except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphonic acid as starting materials.
[0136] Example 8
[0137] Composite particles BA were obtained in the same manner as in Example 1, except that 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of phenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0138] Example 9
[0139] Composite particles BB were obtained in the same manner as in Example 1, except that 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of diphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0140] Example 10
[0141] Composite particles BC were obtained in the same manner as in Example 1, except that 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of triphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0142] Example 11
[0143] Composite particles BD were obtained in the same manner as in Example 1, except that 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphonic acid as starting materials, in addition.
[0144] Example 12
[0145] Composite particles BE were obtained in the same manner as in Example 1, except that: in addition to using 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphoric acid as starting materials.
[0146] Example 13
[0147] Composite particles BF were obtained in the same manner as in Example 1, except that 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphinic acid as starting materials.
[0148] Example 14
[0149] Composite particles BG were obtained in the same manner as in Example 1, except that 1.0 g of activated alumina (D 50 : 3.0μm, BET specific surface area: 300m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphonic acid as starting materials.
[0150] Example 15
[0151] Composite particles CA were obtained in the same manner as in Example 1, except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50 : 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of phenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0152] Example 16
[0153] Composite particles CB were obtained in the same manner as in Example 1, except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50 : 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of diphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0154] Example 17
[0155] Composite particles CC were obtained in the same manner as in Example 1, except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50 : 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of triphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0156] Example 18
[0157] Composite particles CD were obtained in the same manner as in Example 1, except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50 : 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphonic acid as starting materials.
[0158] Example 19
[0159] Composite particles CE were obtained in the same manner as in Example 1, except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50: 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphoric acid as starting materials.
[0160] Example 20
[0161] Composite particles CF were obtained in the same manner as in Example 1, except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50 : 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphinic acid as starting materials.
[0162] Example 21
[0163] Composite particles CG were obtained in the same manner as in Example 1 except that 1.0 g of kaolinite (Al2Si2O5(OH)4, D 50 : 1.0μm, BET specific surface area: 120m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphonic acid as starting materials.
[0164] Example 22
[0165] Composite particles DA were obtained in the same manner as in Example 1 except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0166] Example 23
[0167] Composite particles DB were obtained in the same manner as in Example 1 except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of diphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0168] Example 24
[0169] Composite particles DC were obtained in the same manner as in Example 1 except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of triphenyl phosphate and 2.5g of phosphonic acid as starting materials.
[0170] Example 25
[0171] Composite particles DD were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphonic acid as starting materials.
[0172] Example 26
[0173] Composite particles DE were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of phosphoric acid as starting materials.
[0174] Example 27
[0175] Composite particles DF were obtained in the same manner as in Example 1 except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphinic acid as starting materials.
[0176] Example 28
[0177] Composite particles DG were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylphosphonic acid as starting materials.
[0178] Example 29
[0179] Composite particles DH were obtained in the same manner as in Example 1 except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 5.0g of phosphoric acid as starting materials.
[0180] Example 30
[0181] Composite particles EA were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenyl phosphate and 2.5g of boric acid as starting materials.
[0182] Example 31
[0183] Composite particles EB were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of boronic acid as starting materials.
[0184] Example 32
[0185] Composite particles EC were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenyl phosphate and 2.5g of methylboric acid as starting materials.
[0186] Example 33
[0187] Composite particles ED were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of methylboronic acid as starting materials.
[0188] Example 34
[0189] Composite particles FA were obtained in the same manner as in Example 1, except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenyl phosphate and 2.5g of bromic acid as starting materials.
[0190] Example 35
[0191] Composite particles FB were obtained in the same manner as in Example 1 except that 1.0 g of pseudo-boehmite (D 50 : 1.8μm, BET specific surface area: 384m 2 / g), 2.5g of phenylphosphonic acid and 2.5g of bromic acid as starting materials.
[0192] Comparative Example 5
[0193] Composite particles GA were obtained in the same manner as in Example 1 except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m2 / g) and 5.0 g of phenylphosphonic acid as starting materials.
[0194] Comparative Example 6
[0195] Composite particles GB were obtained in the same manner as in Example 1 except that 1.0 g of aluminum hydroxide (D 50 : 3.0μm, BET specific surface area: 205m 2 / g) and 5.0g of diphenyl phosphate as starting materials.
[0196] Fabrication of positive electrode
[0197] Examples 1 to 35 and Comparative Examples 2 to 6
[0198] LiCoO2, acetylene black, composite particles listed in Table 1, metal hydroxide particles or flame retardants (composite particles, metal hydroxide particles, particle mixtures or flame retardants are collectively referred to as heat reduction or suppression additives), and polyvinylidene fluoride as a binder are dispersed and mixed in the form of solvent-free dry powder (solid content) in N-methyl-2-pyrrolidone solvent to prepare a positive electrode mixture slurry. The slurry is coated on one or both surfaces of the aluminum current collector so that the dried mixture coating amount (surface density) is 20.0 mg / cm 2 and then pressed with a roll press so that the positive electrode mixture layer density was 4.15 g / cc to form a positive electrode mixture layer.
[0199] Comparative Example 1
[0200] A positive electrode was manufactured in the same manner as in Example 1, except that LiCoO2, acetylene black and polyvinylidene fluoride were dispersed and mixed in an N-methyl-2-pyrrolidone solvent as dry powders (solid content) not containing a solvent at a mass ratio of 97.7:1.0:1.3 to prepare a positive electrode mixture slurry.
[0201] Fabrication of negative electrode
[0202] Examples 1 to 35 and Comparative Examples 1 to 6
[0203] Artificial graphite, sodium salt of carboxymethyl cellulose (CMC) and aqueous dispersion of styrene-butadiene copolymer were dissolved and dispersed in an aqueous solvent in a mass ratio of 97.5:1.0:1.5 of dry powder (solid content) without solvent to prepare a negative electrode mixture slurry. The negative electrode mixture slurry was applied on one or both surfaces of a copper foil as a negative electrode current collector and dried so that the dried mixture coating amount (surface density) was 15.0 mg / cm 2and then pressed with a roll press to produce a negative electrode so that the negative electrode mixture layer density was 1.65 g / cc.
[0204] Manufacturing of rechargeable battery cells
[0205] Examples 1 to 35 and Comparative Examples 1 to 6
[0206] A plurality of positive electrodes and a plurality of negative electrodes are stacked with a polypropylene porous separator between the positive electrode and the negative electrode to have a battery design capacity of 300 mAh, thereby manufacturing an electrode stack. As the positive electrode and the negative electrode placed inside the electrode stack, a mixture layer formed on both surfaces of the current collector is used, and for the positive electrode or the negative electrode disposed on the outermost layer, a mixture layer formed only on one surface is used. For example, an electrode plate with an area of 8.5 cm 2 The positive electrode (mixture layers are formed on both surfaces, 5 pieces) and the electrode plate area is 10.0 cm 2 A negative electrode (4 sheets with a mixture layer formed on both surfaces, 2 sheets with a mixture layer formed on one surface) was prepared. A rechargeable battery cell before initial charge was manufactured by welding a nickel lead and an aluminum lead to the negative electrode and the positive electrode of the electrode stack, respectively, accommodating the electrode stack in an aluminum laminate film and leading the leads to the outside, injecting an electrolyte therein, and sealing the aluminum laminate film under reduced pressure. The electrolyte was prepared by dissolving 1.3M LiPF6 and 1% by mass of vinylene carbonate in a mixed solvent of ethylene carbonate / dimethyl carbonate / fluoroethylene carbonate in a volume ratio of 15:80:5.
[0207] Evaluation of heat suppression additives
[0208] The heat-generating suppressing additives used in the Examples and Comparative Examples were evaluated as follows.
[0209] Elemental analysis
[0210] Quantitative analysis was performed using an inductively coupled plasma optical emission spectrometer (ICP-AES, Agilent Technologies, Inc., Agilent 5110VDV model) according to JIS K0116:2014, and Al element, P element, B element and Br element included in the composite particles, metal hydroxide particles or radical supplementer were quantitatively analyzed.
[0211] BET surface area
[0212] The specific surface area (BET specific surface area calculated based on an adsorption isotherm measured by adsorption of water vapor) of the metal hydroxide particles or composite particles is measured in accordance with JIS K6217-2 using a gas adsorption amount measuring device (Microtrack, BELSORP).
[0213] The amount of gas desorbed
[0214] Thermal desorption gas mass spectrometry (TDS-MS) was performed as follows by measuring and analyzing the respective desorption amounts of methane (CH4) molecules, methanol (CH3OH) molecules, benzene (C6H6) molecules, diphosphorus (P2) molecules and water (H2O) molecules using a thermal desorption gas mass spectrometer (TDS-1200, ESCO Co., Ltd.).
[0215] In TDS, the negative electrode active material is set by using a sample stage made of quartz and a sample dish made of SiC. In addition, the heating rate is 60°C / min. The temperature rise is controlled by monitoring the temperature on the sample surface. In addition, the weight of the sample is 1 mg, which is corrected by the actual weight. A quadrupole mass spectrometer is used for detection, and the voltage applied thereto is 1000V.
[0216] TDS is used to measure the amount (μmol / g) of each gas desorbed from metal hydroxide particles or composite particles during a temperature increase from 80°C to 1400°C. The mass number [M / z] used to analyze the measurement is 16 for CH4, 18 for H2O, 32 for CH3OH, 62 for P2, and 78 for C6H6, where the gas corresponding to the mass number is each of the above substances. Here, regarding the gas amount of H2O, the amount of desorbed H2O (MS2) is obtained using the integrated value only from 80°C to 200°C in the entire temperature range.
[0217] Evaluation of particle size
[0218] The particle size of the composite particles or metal hydroxide particles is represented by the 50% integral value D of the particle size distribution based on the particle size volume in the particle size distribution obtained by the laser diffraction / scattering method. 50 Make an evaluation. 50 The measurement was performed using the following equipment and conditions.
[0219] Measuring device: Laser diffraction / scattering particle size distribution measuring device MT3300 (manufactured by Micro Track Bell)
[0220] Transparency: Transparent
[0221] Shape: Non-spherical
[0222] Cycle speed: 7
[0223] Measuring time: 30 seconds
[0224] Repetitions: 3
[0225] Refractive Index:
[0226] a. Composite particles, metal hydroxide particles or particle mixtures: 1.65
[0227] b. Ethanol solvent: 1.36
[0228] Evaluation of rechargeable battery cells
[0229] Cycle characteristics
[0230] The rechargeable battery cells according to Examples 1 to 35 and Comparative Examples 1 to 6 were charged to 4.4V at a constant current at a design capacity of 0.1CA in a 25°C thermostat, and were still charged to 0.05CA at a constant voltage at 4.4V. Subsequently, the cell was discharged to 3.0V at a constant current at 0.1CA. In addition, in a 25°C thermostat, under the conditions of a charge cutoff voltage of 4.4V and a discharge cutoff voltage of 3.0V, the initial discharge capacity of the cell after the first cycle was measured by constant current charging at 0.2CA, constant voltage charging at 0.05CA, and constant current discharging at 0.2CA. Under the conditions of a charge cutoff voltage of 4.3V and a discharge cutoff voltage of 3.0V, the rechargeable battery cell was charged and discharged for 200 cycles at 45°C by constant current charging at 0.5CA, constant voltage charging at 0.05CA, and constant current discharging at 0.5CA to test the cycle life. After 200 cycles, the discharge capacity of the battery under constant current charge of 0.2 CA, constant voltage charge of 0.05 CA, and discharge of 0.2 CA was measured and divided by the initial discharge capacity to obtain the capacity retention rate after 200 cycles.
[0231] Heating test
[0232] The rechargeable battery cells according to Examples 1 to 35 and Comparative Examples 1 to 6 were charged to 4.4V at a constant current with a design capacity of 0.1CA in a 25°C thermostat, and charged to 0.05CA at a constant voltage of 4.4V. Subsequently, the battery was discharged to 3.0V at 0.1CA at a constant current. In addition, in a 25°C thermostat, constant current charging at 0.2CA, constant voltage charging at 0.05CA, and constant current discharge at 0.2CA were performed as 1 cycle under the conditions of a charge cut-off voltage of 4.4V and a discharge cut-off voltage of 3.0V, and the cell was charged to 4.4V at a constant current / constant voltage again, and it was used as an initial cell. These rechargeable battery cells were placed in a thermostat heated to 165°C for 1 hour, and the case where the voltage of the battery cell became 4.2V or less was regarded as "abnormal occurrence", and the abnormal occurrence rate was evaluated by 10 battery tests.
[0233] Acupuncture test
[0234] The pin penetration test was conducted by centrally penetrating the initial cell with a nail having a diameter of 3 mm at 1 mm / s. The case where the external temperature of the cell reached 50°C or higher 5 seconds after penetration with the nail was considered as "abnormal occurrence", and the abnormal occurrence rate was evaluated in 10 battery tests.
[0235] Overcharge test
[0236] The above initial cells were further charged to 12 V at a constant current at 3CA, and then charged at a constant voltage for 10 minutes after reaching 12 V. The case where the external temperature of the battery cell reached 50°C or higher was regarded as "abnormality occurrence", and the abnormality occurrence rate was evaluated by 10 battery tests.
[0237] Evaluation results
[0238] The types and physical properties of the heat generation suppressing additives used in the above examples and comparative examples are shown in Table 1. In addition, the evaluation results of the rechargeable battery cells of Examples 1 to 35 and Comparative Examples 1 to 6 are summarized in Table 2.
[0239] (Table 1)
[0240]
[0241]
[0242]
[0243]
[0244] (Table 2)
[0245]
[0246]
[0247]
[0248] The discharge capacity retention rates of the rechargeable battery cells manufactured in Example 26, Comparative Example 1, and Comparative Examples 3 to 5 shown in Tables 1 and 2 are graphs shown in FIG. Figure 1 middle.
[0249] Confirmation of exothermic behavior in the presence of charged positive electrode and electrolyte
[0250] The initial cells of the fully charged rechargeable battery cells manufactured in Example 26 and Comparative Example 1 and Comparative Examples 3 to 5 shown in Tables 1 and 2 were disassembled in a glove box, and the positive electrodes were washed with a dimethyl carbonate solvent and dried, and the obtained positive electrodes were used as “charged positive electrodes”.
[0251] 2.0 mg of the "charged positive electrode" and 1.0 mg of the same electrolyte as used in manufacturing the rechargeable battery cell were placed in a special airtight container, caulking was performed, and then the temperature was increased at a heating rate of 5 K / min using a differential scanning calorimeter, DSC (manufactured by Hitachi High-Tech Sciences) in accordance with JIS K7121 to evaluate the heat release behavior. The results are shown in Figure 2 middle.
[0252] Overview of Examples and Comparative Examples
[0253] As can be seen from the results in Table 2, in Examples 1 to 35, even under conditions where the internal temperature of the battery is likely to rise (high voltage charging under high temperature conditions, external impact from nail penetration, or overcharging), the incidence of abnormalities caused by the temperature rise inside the battery can be sufficiently reduced or suppressed. Figure 2 In the exothermic behavior shown in , this effect can also be shown by the substantial disappearance of the exothermic peak between 150° C. and 250° C.
[0254] On the contrary, in Comparative Example 1 not including the heat-suppressing additive, in Comparative Examples 2 to 4 including only metal hydroxide or flame retardant, and in Comparative Examples 5 and 6 including composite particles of combined metal hydroxide and flame retardant but the content of phosphorus element in the particles, or the sum of the content of phosphorus element and boron element or bromine element is less than 18wt%, the abnormality occurrence rate (e.g., nail penetration test abnormality occurrence rate) exceeds 40%. On the other hand, in each example, two types of flame retardants are added in equal amounts, but not limited to this form, and if the content of phosphorus element, the sum of phosphorus element and boron element or bromine element in the composite particles is greater than or equal to about 18wt% and less than or equal to about 30wt%, the effect of the present disclosure can be exhibited.
[0255] In addition, from Table 2 and Figure 1 From the results, in Comparative Examples 2 to 4, the cycle characteristics are reduced by including various heat-suppressing additives compared to Comparative Example 1 which does not include the heat-suppressing additive, but in Examples 1 to 35, the cycle characteristics substantially the same as those of Comparative Example 1 can be maintained.
[0256] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the present disclosure is not limited to the disclosed example embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A composite particle for a non-aqueous electrolyte rechargeable battery, the composite particle comprising: Metal hydroxide and flame retardant components, The flame retardant component includes at least one of phosphorus, phosphorus and boron, and phosphorus and bromine, and One of a content of phosphorus element, a sum of contents of phosphorus element and boron element, and a sum of contents of phosphorus element and bromine element is greater than or equal to 18 wt % and less than or equal to 30 wt % based on 100 wt % of the composite particles.
2. The composite particles according to claim 1, wherein The amount of P2 desorbed from 80°C to 1400°C of the composite particle MS1 is greater than or equal to 600×10 -6 mol / g and less than or equal to 2000×10 -6 mol / g; and The amount of H2O desorbed from the composite particle at 80°C to 200°C is greater than or equal to 50×10 -6 mol / g and less than or equal to 1000×10 -6 mol / g.
3. The composite particles according to claim 1, wherein The amount of CH4 desorbed from the composite particle at 80°C to 1400°C is greater than or equal to 30×10 -6 mol / g and less than or equal to 400×10 -6 mol / g; The amount of CH3OH desorbed from the composite particles at 80°C to 1400°C is greater than or equal to 500×10 -6 mol / g and less than or equal to 2500×10 -6 mol / g; and The amount MS5 of C6H6 desorbed from the composite particles from 80°C to 1400°C is greater than or equal to 100×10 -6 mol / g and less than or equal to 2500×10 -6 mol / g.
4. The composite particles according to claim 2, wherein The ratio of the amount of desorbed gas satisfies formula (1): 0.6≤(MS1 / MS2)≤10.0…(1).
5. The composite particles according to claim 1, wherein The BET specific surface area of the composite particles is greater than or equal to 8 m 2 / g and less than or equal to 80m 2 / g. The composite particles according to claim 1 , wherein The 50% integral value D of the volume-based particle size distribution of the composite particles 50 Greater than or equal to 0.05 μm and less than or equal to 10 μm.
7. The composite particles according to claim 1, wherein The metal hydroxide includes at least one of aluminum hydroxide, pseudoboehmite, boehmite, activated alumina and kaolinite.
8. The composite particles according to claim 1, wherein The aluminum element content is greater than or equal to 1 wt % and less than or equal to 30 wt % based on 100 wt % of the composite particles.
9. A positive electrode for a non-aqueous electrolyte rechargeable battery, the positive electrode comprising: a positive electrode current collector and a positive electrode mixture layer on the positive electrode current collector, Wherein, the positive electrode mixture layer includes a positive electrode active material and the composite particles according to claim 1 .
10. A non-aqueous electrolyte rechargeable battery, comprising: Positive electrode, negative electrode, separator and non-aqueous electrolyte, Wherein, the positive electrode is the positive electrode according to claim 9.
11. A method for preparing composite particles for non-aqueous electrolyte rechargeable batteries, the method comprising the steps of: mixing metal hydroxide particles and a flame retardant; as well as The mixed metal hydroxide particles and the flame retardant are heated to prepare the composite particles according to claim 1 .
Citation Information
Patent Citations
Lithium secondary battery
JP2011159484A
Lithium ion battery
JP2011258481A
Electrolyte, battery, battery pack, electronic apparatus, electric vehicle, power storage device and power system
JP2016162528A
Elevator with storage shelf
JP2023131857A
Aid device for turning patient posture and bed for turning patient posture
KR1020240055545A